Baseline study of per- and polyfluoroalkyl substances (PFAS) occurrence in surface raw water and treated drinking water - Okta Lian Atikah; Haruki Agustina; Tri Edhi Budhi Soesilo (Environmental and Materials, 2026)
Background: Per- and polyfluoroalkyl substances (PFAS) are emerging contamintants that has become global concern due to their adverse environmental and health impacts. However, information regarding PFAS contamination in river-derived drinking water systems in developing countries, including Indonesia, remains very limited. This study aimed to analyze nineteen PFAS compounds in raw water, treated drinking water, and Reverse Osmosis (RO) reject water from the Mookervart Drinking Water Treatment Plant, Jakarta, Indonesia, evaluate its potential human risk, and mitigation strategies. Methods: Analysis of water samples was done using LC-MS/MS. Findings: Nine PFAS detected with ∑PFAS concentrations reaching 758.94 ng/L and 1219.35 ng/L in raw water and drinking water, respectively. Long-chain PFAS compounds, particularly PFOS and PFOA, were effectively removed by the RO unit, highlighting the importance of advanced treatment technologies in reducing potential human exposure risks. In contrast, PFBA remained substantially high in treated drinking water and exceeded the European Union drinking water threshold. Conclusion: These findings emphasize the importance of strategic PFAS management through source-control mitigation, establishment of drinking water standards, and implementation of Best Available Techniques (BAT). Novelty/Originality of this article: This study provide first baseline data on PFAS contamination in surface water-derived drinking water in Jakarta supporting future PFAS monitoring and mitigation efforts.